First report of Pseudoperonospora cubensis causing downy mildew of Trichosanthes cucumerina in Malaysia - Salati, Mansour; Wong, Mui Yun; Meon, Sariah; Nik Hassan, Nik Masdek (American Phytopathological Society, 2010)
In December 2008, infected leaves of T. cucumerina were observed in commercial cucurbit farms located in Pontian, Johor (south of West Malaysia). Bright yellow and small necrotic lesions were observed on the adaxial surface of the leaves, whereas sporangiophores were observed on pale yellowish brown-to-brown lesions on the abaxial surface. The pathogen was identified as P. cubensis based on the morphological and molecular characteristics of the isolates. This is thought to be the first report of P. cubensis causing downy mildew of T. cucumerina in Malaysia.